EFEK KEDALAMAN PELAT TEMBAGA PADA PERKERASAN ASPAL TERHADAP TEMPERATUR LEMPENG DAN DAYA LISTRIK YANG DIPEROLEH OLEH GENERATOR TERMOELEKTRIK - Satria Lanuri (Fakultas Teknik - Universitas Riau, 2022)
Solar radiation can be used to produce electrical energy using thermoelectric generators. A thermoelectric generator is a p-type and n-type semiconductor that converts heat to solar radiation into electrical energy. In this study, asphalt road was used as a heat sink to collect solar heat. Asphalt heat will be delivered to the thermoelectric side of the generator using a copper plate. In this study, copper plates were implanted in asphalt with different heights, namely 2 cm, 4 cm, and 6 cm from the asphalt surface. The results showed that the hot side temperature of copper with a depth of 2 cm faster absorbs heat because it is closer to the asphalt surface. When the highest value of solar radiation is 987 W / m at 12:00 p.m., the hot side temperature also experiences the highest temperature of 38.1 ̊C. While the peak temperature found on the plate with a depth of 4 cm is 14.30 at 37.6 .6C, and for the 6 cm depth plate, the peak temperature is 37.9 ̊C at 3:00 p.m. Plates with a depth of 2 cm can produce greater power than those on 4 cm and 6 cm depth plates. This happens because the heat received by the scale is 4 cm deep and 6 cm slower than the plate with a depth of 2 cm. So, leaves with a depth of 2 cm produce greater electrical power at higher plate temperatures.